The slower cyclist's speed is 10 mph, and the faster cyclist's speed is 20 mph.
Let's denote the speed of the slower cyclist as "x" miles per hour (mph). Since the faster cyclist is going twice as fast, their speed would be "2x" mph.
When they start riding towards each other, their combined speed is the sum of their individual speeds:
Combinedspeed = x + 2x
= 3x mph.
We are given that they meet 3 hours later and travel a totaldistance of 90 miles.
The distance each cyclist travels can be calculated using the formula:
Distance = Speed × Time.
For the slower cyclist:
Distance = x × 3
Distance = 3x miles.
For the fastercyclist:
Distance = 2x × 3
Distance= 6x miles.
Since they are 90 miles apart and have traveled a total distance of 90 miles when they meet, we can set up an equation:
Distance of slower cyclist + Distance of faster cyclist = Total distance
3x + 6x = 90.
Simplify the equation:
9x = 90.
Divide both sides by 9:
x = 10.
So, the speed of the slower cyclist is 10 mph, and the speed of the faster cyclist is 2x which is 20 mph.
To learn more on Speed click:
#SPJ12
Answer:
DE is the common side in the two triangles
Explanation:
The side of the triangle is named based on its start and end points
A triangle is named based on its three vertices where each two vertices would join forming a side
For ΔDEC, the sides are:
DE, EC and DC
For ΔEDB, the sides are:
ED, DB and EB
By comparing the two triangles, we would find that DE is the common side in both triangles
Note: The visual illustration is in the attached image
Hope this helps :)
-4x + y = -1
A) (3,1)
B) (-1,3)
C) (-1,-3)
D) (1,3)
Hi Brainiac
-2x+y=1
-4x+y=-1
We need to solve -2x+y=1 for y
Now let's start by adding 2x to both sides
-2x+y+2x=1+2xy=2x+1
Substitute 2x+1 for y in -4x+y=-1
-4x+y=-1
-4x+2x+1=-1
-2x+1=-1
Add -1 to both sides
-2x+1-1=-1-1
-2x=-2
Now divide both sides by -2 so we can fine the value for x
-2x/-2= -2/-2
x=1
The last step is to substitute 1 for x in y=2x+1
y=2x+1
y=(2)(1)+1
y= 2+1
y= 3
Answer : D , (1,3)
Good night :)
Value of given multiply a² - b
Given that;
(a+√b)(a-√b)
Find:
Value of given multiply
Computation:
(a+√b)(a-√b)
Formula used;
⇒ (a + b)(a - b) = a² - b²
So,
⇒ (a+√b)(a-√b)
⇒ (a)² - (√b)²
⇒ a² - b
Learn more:
Answer:
Step-by-step explanation:
B. 28x
C. (4.7)x
D. 4(7+x)